ERYTHEMA NODOSUM: VASCULITIS OR PANNICULITIS? - Boris Sergeyevich Belov; O N Egorova; S G Radenska-Lopovok; R M Balabanova; E G Sazhina; M E Tsanyan (Современная ревматология)
Erythema nodosum (EN) as an individual entity has been known for more than 200 years. The long-term study of the disease by rheumatologists, pulmonologists, dermatologists, and other specialists has allowed them to state a variety of etiotropic factors and polymorphism of its clinical symptomatology. Up to now, the discussion of the histopathomorphological nature of EN (vasculitis or panniculitis?) has been continued. The described case makes it possible to regard EN as a manifestation of vasculitis to a greater extent. Further clinical studies are needed depending on the stage of the disease and etiotropic factors.